2019
DOI: 10.1161/circinterventions.119.007830
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Versus Medical Management in Patients With Prior Coronary Artery Bypass Surgery With a Non-ST Segment Elevation Acute Coronary Syndrome

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Moreover, the finding in the comparison of the randomised trial groups that health outcomes were not different with invasive management versus conservative management supports the notion that enrolment rates could be increased by education of physicians and patients. 21 Our trial results broadly reflect equipoise between the randomised strategies which should enhance confidence to support enrolment into a future randomised trial.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the finding in the comparison of the randomised trial groups that health outcomes were not different with invasive management versus conservative management supports the notion that enrolment rates could be increased by education of physicians and patients. 21 Our trial results broadly reflect equipoise between the randomised strategies which should enhance confidence to support enrolment into a future randomised trial.…”
Section: Discussionsupporting
confidence: 57%
“…Patients with prior CABG have been excluded from many important clinical trials including VINO 32 and RITA3 24,[33][34][35][36] and only contributed to small numbers of patients in other ACS clinical trials (in OASIS-5: 1643 of 20,078 patients, in LIPSIA-NSTEMI: 41 of 600 patients, in Italian elderly ACS: 29 of 313, and in After Eighty Study: 76 of 457 patients). [37][38][39][40][41][42] Apart from a recently published pilot study where Lee et al 43 reported 12-month outcome data from 60 prior-CABG patients (invasive group, n¼31; medical group, n¼29), no major clinical trials exclusively examined clinical outcomes of an invasive versus medical approach in patients who presented with acute MI and had prior CABG. 40 In our study, only half of prior CABG patients underwent invasive coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in interventional therapy, most patients are treated aggressively. However, several randomized controlled trials (RCTs) failed to show appreciable benefits in reducing major cardiac events with the invasive strategy compared with the conservative management (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The invasive strategy also carries a certain risk for procedure-related myocardial infarction (MI) and a high risk of bleeding (20).…”
Section: Introductionmentioning
confidence: 99%